2021
DOI: 10.1111/ina.12951
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a novel personal comfort system on thermal comfort, physiology and perceived indoor environmental quality, and its health implications ‐ Stimulating human thermoregulation without compromising thermal comfort

Abstract: Humans spend 80%-90% of their time indoors. 1,2 Hence, indoor environmental conditions have a fundamental impact on human health, comfort and productivity. The primary purpose of indoor temperature control is to provide thermal comfort, the so-called "condition of mind that expresses satisfaction with the thermal environment". 3 The general notion is that thermal comfort occurs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…8 Moreover, some studies revealed that the occupants are prone to report differently thermal comfort results if the control of the environment belongs themselves. [9][10][11] For instance, in a study of Yun,11 the comfort temperature of the group with high perceived control was 0.9°C higher than the group with low perceived control in summer season. In addition, several studies also stated that the thermal sensation of the occupants is related primarily to the psychophysical dynamics of thermal alliesthesia, which are related to qualities of pleasantness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, some studies revealed that the occupants are prone to report differently thermal comfort results if the control of the environment belongs themselves. [9][10][11] For instance, in a study of Yun,11 the comfort temperature of the group with high perceived control was 0.9°C higher than the group with low perceived control in summer season. In addition, several studies also stated that the thermal sensation of the occupants is related primarily to the psychophysical dynamics of thermal alliesthesia, which are related to qualities of pleasantness.…”
Section: Introductionmentioning
confidence: 99%
“…By the given information, the occupants in both rooms felt warm even though the ambient temperatures were different 8 . Moreover, some studies revealed that the occupants are prone to report differently thermal comfort results if the control of the environment belongs themselves 9–11 . For instance, in a study of Yun, 11 the comfort temperature of the group with high perceived control was 0.9°C higher than the group with low perceived control in summer season.…”
Section: Introductionmentioning
confidence: 99%
“…[23] While a positive energy balance is necessary to counteract obesity, most recent research assumes that long exposure to thermal neutral environments, does the exact opposite. [23,24,[32][33][34] Several studies were able to show that cold and warmth both effect the metabolic health and mild colds to positively increase the energy metabolism without shivering. This non-shivering thermogenesis (NST) increases energy expenditure in temperatures between 14 -16°C for lightly clothed, lean adult, and in temperatures as high as 19°C and regular exposure for two hours per day for six weeks to 17°C, as shown in a study done by Yoneshiro, according to Lichtenbelt, et al (2017) [23].…”
Section: Evaluating Healthmentioning
confidence: 99%
“…The implementation of time-varying indoor set-point temperatures can contribute to reducing buildings' energy consumption and promoting their energy flexibility 1,2 . Heating and cooling setpoint temperature modulations can also be useful for enhancing building occupants' comfort [3][4][5][6][7][8] , well-being 9 , and health [10][11][12] . However, thermal comfort has been mostly studied under steady-state conditions and near neutrality 8,13 ; the effect of the time-of-day on human thermal perception has been even less often addressed 14 .…”
mentioning
confidence: 99%